Selection of preferred sweet sorghum cultivars and their pretreatment optimisation for bio-ethanol production - McIntosh, Paul Andrew (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.